Nutritiology And Proper Nutrition - Shamuratova N.Sh; Shermetov R.A; Nurullayev S.X (Zien Journals, 2024)
This article delves into the field of nutritiology, aiming to provide a thorough understanding of proper nutrition and its impact on human health. Through an analysis of existing literature, the article explores dietary guidelines, the role of macronutrients and micronutrients, and the methods employed in nutritional research. The results section presents key findings, leading to a discussion on the implications for health. The article concludes with insights and suggestions for individuals seeking to enhance their nutritional well-being
Keywords: Nutritiology; nutrition; dietary guidelines; health